The concept of Islamic banking from the Islamic worldview - Mohd Yunus, Saidatolakma; Kamaruddin, Zuraidah; Embong, Rahimah (Human Resource Management Academic Research Society (HRMARS), 2018)
Islamic banks are required to run their business activity with full conformity to Shariah. They should not borrow money on interest nor keep their surplus cash in interest bearing account as well as should not involve in any prohibited business deals. Even if the business activities are permissible, the borrowings may be based on riba (usury), the surplus is kept in interest bearing accounts and so on. Hence, this article aims to offer an alternative to liberate Muslim investors and small managers from the sinful action of dealing with those banking business activities.